Refinement of Initial Information in Automated Control Systems While Using Constraint Equations - V. A. Yanitsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper provides some changes and additions to the known method for controlling reliability and refining the initial information in case of its automatic processing at the expense of usage of additional information which is contained in the equations of material and power balances, other dependences. An application of the modified control method makes it possible significantly to expand field of its application. Calculations for evaluation of the given method efficiency have been carried out in the paper.